Candidate Gene Sequencing of SLC11A2 and TMPRSS6 in a Family with Severe Anaemia: Common SNPs, Rare Haplotypes, No Causative Mutation - Kloss-Brandstätter, Anita; Erhart, Gertraud; Lamina, Claudia; Meister, Bernhard; Haun, Margot; Coassin, Stefan; Seifert, Markus; Klein-Franke, Andreas; Paulweber, Bernhard; Kedenko, Lyudmyla; Kollerits, Barbara; Swinkels, Dorine W.; et al. (PLOS ONE, 2012)
Background Iron-refractory iron deficiency anaemia (IRIDA) is a rare disorder which was linked to mutations in two genes (SLC11A2 and TMPRSS6). Common polymorphisms within these genes were associated with serum iron levels. We identified a family of Serbian origin with asymptomatic non-consanguineous parents with three of four children presenting with IRIDA not responding to oral but to intravenous iron supplementation. After excluding all known causes responsible for iron deficiency anaemia we searched for mutations in SLC11A2 and TMPRSS6 that could explain the severe anaemia in these children. Methodology/Results We sequenced the exons and exon–intron boundaries of SLC11A2 and TMPRSS6 in all six family members. Thereby, we found seven known and fairly common SNPs, but no new mutation. We then genotyped these seven SNPs in the population-based SAPHIR study (n = 1,726) and performed genetic association analysis on iron and ferritin levels. Only two SNPs, which were top-hits from recent GWAS on iron and ferritin, exhibited an effect on iron and ferritin levels in SAPHIR. Six SAPHIR participants carrying the same TMPRSS6 genotypes and haplotype-pairs as one anaemic son showed lower ferritin and iron levels than the average. One individual exhibiting the joint SLC11A2/TMPRSS6 profile of the anaemic son had iron and ferritin levels lying below the 5th percentile of the population's iron and ferritin level distribution. We then checked the genotype constellations in the Nijmegen Biomedical Study (n = 1,832), but the profile of the anaemic son did not occur in this population. Conclusions We cannot exclude a gene-gene interaction between SLC11A2 and TMPRSS6, but we can also not confirm it. As in this case candidate gene sequencing did not reveal causative rare mutations, the samples will be subjected to whole exome sequencing.